Preparation method of MXene / LDHs heterojunction self-assembly anticorrosive paint
By developing a self-assembled anti-corrosion coating based on MXene/LDHs heterostructures, the problem of existing coatings being easily damaged in extreme environments has been solved, achieving multifunctional anti-corrosion properties of the coating and reducing the corrosion risk of marine engineering materials.
Patent Information
- Application Number
- CN202411227500.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-03
AI Technical Summary
Existing anti-corrosion coatings are prone to damage under the high temperature, high humidity, high salinity, strong ultraviolet radiation, and seasonal typhoon conditions of the South China Sea. This leads to the "large cathode and small anode" phenomenon in localized areas caused by corrosive media, further aggravating the corrosion of the steel structure substrate and failing to meet the requirements for long-term anti-corrosion.
The preparation method of MXene/LDHs heterojunction self-assembled anti-corrosion coating adopts the following approach: by applying an external electric field in a liquid battery cell, MXene and LDHs particles undergo an electrochemical reaction between the cathode and anode regions to form a stable heterostructure. The combination of the physical barrier effect of MXene and the ion adsorption and exchange effect of LDHs enhances the anti-corrosion performance of the coating.
The coating achieves multifunctional anti-corrosion properties, including targeted adsorption, delayed diffusion of corrosive media, and enhanced substrate passivation, thereby reducing the corrosion risk of marine engineering materials.
Smart Images

Figure CN119286286A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of marine engineering anti-corrosion, and in particular to a method for preparing a MXene / LDHs heterojunction self-assembled anti-corrosion coating. Background Art
[0002] In the marine environment, the erosion of sea breeze and salt spray significantly reduces the safe service life of engineering structures. The corrosion of offshore facilities and equipment is more serious, and problems such as rust, cracking, and coating peeling often occur, and even cause safety accidents such as fire and collapse.
[0003] In the prior art, zinc-rich primer, epoxy micaceous iron intermediate paint and polyurethane topcoat are commonly used as anti-corrosion coatings. However, under the high temperature, high humidity, high salt, strong ultraviolet rays and seasonal typhoon environment of the South China Sea, the long-term effectiveness of the coating still cannot meet the engineering requirements. When the coating is damaged, cracked and other problems occur, the corrosive medium will cause the "large cathode and small anode" phenomenon locally, further aggravating the corrosion of the steel structure base at the damaged location and causing more serious rust perforation problems. Summary of the invention
[0004] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a method for preparing a MXene / LDHs heterojunction self-assembled anti-corrosion coating, which can improve the corrosion resistance of the coating and reduce the corrosion risk of marine engineering materials.
[0005] According to some embodiments of the present invention, the preparation method of the MXene / LDHs heterojunction self-assembled anti-corrosion coating comprises:
[0006] S1: adding MXene to an electrolyte solution, separating and drying the MXene in the electrolyte solution to obtain a MXene precipitate, adding LDHs to an electrolyte solution, separating and drying the LDHs in the electrolyte solution to obtain a LDHs precipitate;
[0007] S2: The dried MXene precipitate is redissolved in a solvent and subjected to ultrasonic dispersion to obtain a MXene solution, and the dried LDHs precipitate is redissolved in a solvent to obtain an LDHs solution;
[0008] S3: using an inert electrode and a DC power supply to make a liquid battery tank, and using an insulating membrane to divide the liquid battery tank into a cathode region and an anode region;
[0009] S4: Add the MXene solution to the cathode area of the liquid battery tank, add the LDHs solution to the anode area of the liquid battery tank, remove the insulating diaphragm and turn on the power supply to make the MXene and LDHs react to form a MXene / LDHs heterojunction;
[0010] S5: Centrifuge the mixed solution in the liquid battery tank, collect the MXene / LDHs heterojunction precipitate, and add the obtained MXene / LDHs heterojunction precipitate to the anti-corrosion coating.
[0011] According to the preparation method of the MXene / LDHs heterojunction self-assembled anti-corrosion coating according to the embodiment of the present invention, there is at least the following beneficial effects: MXene and LDHs are added to the electrolyte solution respectively, and the functional groups on the surfaces of MXene and LDHs can be adsorbed with the ions in the electrolyte solution. In the liquid battery tank, the surface of MXene has a negative charge and the surface of LDHs has a positive charge. By applying an external electric field, the negatively charged MXene particles will move toward the positive electrode, and the positively charged LDHs particles will move toward the negative electrode. Under the action of the electric field, the MXene and LDHs particles undergo an electrochemical reaction between the cathode region and the anode region. The MXene and LDHs particles with opposite charges attract each other under the action of the electric field and self-assemble into a heterostructure to form a stable bond. Therefore, the physical barrier effect of MXene combined with the ion adsorption and exchange of LDHs can enhance the corrosion resistance of the coating. The interaction between the two can transform the anti-corrosion function of the coating from physical barrier to active adsorption and exchange, so that the coating attached to the metal has a more comprehensive and intelligent protection capability when facing corrosive ions, and realizes multifunctional anti-corrosion performance of targeted adsorption of corrosive media, delayed diffusion of corrosive media and enhanced substrate passivation, thereby reducing the corrosion risk of marine engineering materials.
[0012] According to some embodiments of the present invention, in S1, the electrolyte solution contains F - , Ca 2+ Mg 2+ 、Zn 2+ and Al 3+ .
[0013] According to some embodiments of the present invention, MXene and F - The molar ratio is greater than 1:5.
[0014] According to some embodiments of the present invention, LDHs and Ca 2+ Mg 2+ 、Zn 2+ and Al 3+ The molar ratio is greater than 1:5.
[0015] According to some embodiments of the present invention, in S1, the electrolyte solution containing MXene is subjected to ultrasonic treatment, static treatment and centrifugation treatment in sequence to obtain a MXene precipitate, and the electrolyte solution containing LDHs is subjected to ultrasonic treatment, static treatment and centrifugation treatment in sequence to obtain an LDHs precipitate.
[0016] According to some embodiments of the present invention, the static treatment time is greater than 24 hours;
[0017] According to some embodiments of the present invention, in S2, the solvent is pure water.
[0018] According to some embodiments of the present invention, in S2, the ultrasonic dispersion time is greater than 5 minutes;
[0019] According to some embodiments of the present invention, in S4, the power supply applies a voltage in a range of 5 volts to 10 volts.
[0020] According to some embodiments of the present invention, in S4, the reaction time of MXene and LDHs is greater than or equal to 6 hours.
[0021] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention is further described below in conjunction with the accompanying drawings and embodiments:
[0023] Figure 1 It is a schematic flow chart of a method for preparing a MXene / LDHs heterojunction self-assembled anti-corrosion coating according to an embodiment of the first aspect of the present invention;
[0024] Figure 2 It is a comparison chart of coating impedance values of specific embodiment 1 of the method for preparing the MXene / LDHs heterojunction self-assembled anti-corrosion coating according to the first aspect of the present invention and a blank control sample;
[0025] Figure 3 This is a comparison chart of chloride ion penetration between specific example 2 of the method for preparing the MXene / LDHs heterojunction self-assembled anti-corrosion coating according to the first aspect of the present invention and a blank control sample;
[0026] Figure 4 It is a schematic diagram of MXene / LDHs heterojunction intelligent coating protection in the application of MXene / LDHs heterojunction in the embodiment of the second aspect of the present invention.
[0027] Reference numerals:
[0028] MXene / LDHs heterojunction coating 100, MXene / LDHs heterojunction 110;
[0029] Ordinary coating 200;
[0030] Matrix 10, chloride ions 20. DETAILED DESCRIPTION
[0031] This section will describe in detail the specific embodiments of the present invention. The preferred embodiments of the present invention are shown in the accompanying drawings. The purpose of the accompanying drawings is to supplement the description of the text part of the specification with graphics, so that people can intuitively and vividly understand each technical feature and the overall technical solution of the present invention, but it cannot be understood as a limitation on the scope of protection of the present invention.
[0032] In the description of the present invention, it should be understood that descriptions involving orientations, such as up, down, front, back, left, right, etc., and orientations or positional relationships indicated are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0033] In the description of the present invention, "several" means one or more, "more" means more than two, "greater than", "less than", "exceed" etc. are understood as not including the number itself, and "above", "below", "within" etc. are understood as including the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing the technical features, and cannot be understood as indicating or implying the relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0034] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.
[0035] refer to Figures 1 to 4 The preparation method of the MXene / LDHs heterojunction self-assembled anti-corrosion coating according to an embodiment of the present invention is described.
[0036] like Figure 1 As shown, the preparation method of the MXene / LDHs heterojunction self-assembled anti-corrosion coating according to the first embodiment of the present invention includes:
[0037] S1: adding MXene to an electrolyte solution, separating and drying the MXene in the electrolyte solution to obtain a MXene precipitate, adding LDHs to an electrolyte solution, separating and drying the LDHs in the electrolyte solution to obtain a LDHs precipitate;
[0038] Specifically, the electrolyte solution contains F - , Ca 2+ Mg 2+ 、Zn 2+ and Al 3+ MXene and F - The molar ratio of LDHs to Ca is greater than 1:5. 2+ Mg 2+、Zn 2+ and Al 3+ The molar ratio is greater than 1:5;
[0039] Specifically, the electrolyte solution containing MXene is subjected to ultrasonic treatment, static treatment and centrifugal treatment in sequence to obtain a MXene precipitate, and the electrolyte solution containing LDHs is subjected to ultrasonic treatment, static treatment and centrifugal treatment in sequence to obtain an LDHs precipitate, wherein the reaction time of the static treatment is greater than 24 hours;
[0040] S2: The dried MXene precipitate is redissolved in a solvent and subjected to ultrasonic dispersion to obtain a MXene solution, and the dried LDHs precipitate is redissolved in a solvent to obtain an LDHs solution;
[0041] Specifically, in order to prevent other impurities in the water from destroying the ions already adsorbed on the surface of MXene and LDHs, pure water is used as the solvent. Thus, by using pure water for ultrasonic dispersion, the MXene and LDHs particles can be effectively re-dispersed and converted into the form of aqueous solution without introducing new ions or impurities, which helps to maintain the ionic state and surface properties of MXene and LDHs, thereby providing a clean environment and a stable material state for the electrochemical reaction and self-assembly in the subsequent steps;
[0042] Specifically, the ultrasonic dispersion time is greater than 5 minutes;
[0043] S3: using an inert electrode and a DC power supply to make a liquid battery tank, and using an insulating membrane to divide the liquid battery tank into a cathode region and an anode region;
[0044] S4: Add the MXene solution to the cathode area of the liquid battery tank, add the LDHs solution to the anode area of the liquid battery tank, remove the insulating diaphragm and turn on the power supply to make the MXene and LDHs react to form a MXene / LDHs heterojunction;
[0045] Specifically, the power supply applied voltage ranges from 5 volts to 10 volts, and the reaction time of MXene and LDHs is not less than 6 hours;
[0046] S5: Centrifuge the mixed solution in the liquid battery tank, collect the MXene / LDHs heterojunction precipitate, and add the obtained MXene / LDHs heterojunction precipitate to the anti-corrosion coating.
[0047] It should be noted that the two-dimensional structure of MXene gives it a large surface area, can provide more barrier interfaces, and has excellent physical barrier properties, which can effectively prevent the penetration and diffusion of external corrosive ions into the coating, thereby protecting the metal substrate. LDHs is a layered double hydroxide with excellent ion adsorption and exchange capabilities, which enables it to interact with the corrosive ions in the surrounding environment on the coating surface, intercept and transform the corrosive ions through ion exchange, and protect the metal substrate in various ways from physical barrier to cathodic protection. However, if they are simply mixed, the two substances will agglomerate and their functions will not be exerted.
[0048] like Figure 4 As shown in the figure, MXene and LDHs are added to the electrolyte solution respectively, and the functional groups on the surfaces of MXene and LDHs can adsorb with the ions in the electrolyte solution. In the liquid battery tank, the surface of MXene carries a negative charge and the surface of LDHs carries a positive charge. By applying an external electric field, the negatively charged MXene particles will move toward the positive electrode, while the positively charged LDHs particles will move toward the negative electrode. Under the action of the electric field, the MXene and LDHs particles undergo an electrochemical reaction between the cathode and anode regions. The MXene and LDHs particles with opposite charges attract each other and self-assemble into a heterogeneous structure under the action of the electric field to form a stable combination. Therefore, the physical barrier effect of MXene combined with the ion adsorption and exchange effect of LDHs can enhance the corrosion resistance of the coating. The interaction between the two can transform the anti-corrosion function of the coating from physical barrier to active adsorption and exchange, so that the coating attached to the metal has a more comprehensive and intelligent protection ability when facing corrosive ions, and realizes the multifunctional anti-corrosion performance of targeted adsorption of corrosive media, delayed diffusion of corrosive media and enhanced substrate passivation, thereby reducing the corrosion risk of marine engineering materials.
[0049] The preparation method of the MXene / LDHs heterojunction self-assembled anti-corrosion coating is described in detail below using two specific embodiments. Specific embodiment one:
[0051] S1: Weigh 50 mg of MXene, 100 mg of LDHs and 100 mg of MgAl-LDHs powder samples, add 50 mg of MXene to 100 mL of 1.5 mol / L NaF solution, add 100 mg of LDHs to 100 mL of 2 mol / L MgSO4 solution, ultrasonically disperse the NaF solution containing MXene and the MgSO4 solution containing LDHs for 5 min, then let stand for 48 hours to fully adsorb ions, centrifuge and collect the corresponding precipitates, dry them in a cool place and collect them for later use;
[0052] S2: Weigh about 50 mg of MXene and about 100 mg of LDHs after drying, weigh two cups of 100 mL of pure water in a beaker, and mark the two cups of pure water as A and B, respectively. Add 50 mg of MXene to beaker A and 100 mg of LDHs to beaker B, and ultrasonically disperse the two cups of solution to prepare aqueous solutions of the two materials.
[0053] S3: A liquid battery tank with a size of 30cm×10cm×10cm is made of insulating plastic. The middle of the liquid battery tank is divided into a cathode area and an anode area by an insulating diaphragm. A titanium mesh inert electrode with a size of 10cm×10cm is placed in each of the two areas. A DC power supply is used as the power supply;
[0054] S4: Add MXene solution to the cathode area, add LDHs solution to the anode area, remove the insulating diaphragm, turn on the power supply, apply 8V DC voltage, and set the reaction time to 8 hours;
[0055] S5: After the reaction is completed, the liquid in the liquid battery tank is centrifuged using a centrifuge to collect the obtained MXene / LDHs heterojunction precipitate, which is dried in a cool place and then collected for later use.
[0056] The MXene / LDHs heterojunction prepared by the preparation method of the MXene / LDHs heterojunction self-assembly anti-corrosion coating is added to the coating. The specific method is as follows: weigh 5g of epoxy resin and 100mg of MXene / LDHs heterojunction, add the MXene / LDHs heterojunction to the epoxy resin, stir for 1 hour to mix them evenly, and obtain an active protective coating.
[0057] A Q235 steel plate with a size of 10 cm × 10 cm was selected. After surface treatment, a new type of coating doped with MXene / LDHs heterojunction and an undoped epoxy resin coating were coated on different areas. The coating thickness was about 200 μm. After coating, the two coatings were dried and accelerated tests were carried out using a neutral salt spray test to test the coating impedance values. The following results were obtained: Figure 2 The results shown in the figure benefit from the MXene barrier effect and the LDHs ion adsorption and exchange effect. Whether in the initial stage of the test or after a long period of salt spray test, the impedance value of the new coating doped with MXene / LDHs heterojunction is significantly higher than that of the blank control sample. Therefore, the new coating doped with MXene / LDHs heterojunction has strong anti-corrosion properties. Therefore, the MXene / LDHs heterojunction plays a key role in improving the performance of the coating. Specific embodiment 2:
[0059] S1: Weigh 100 mg of MXene and 200 mg of CaZn-LDHs respectively, add 100 mg of MXene to 100 mL of 3 mol / L NaF solution, add 200 mg of LDHs to 100 mL of 4 mol / L ZnSO4 solution, ultrasonically disperse the NaF solution containing MXene and the MgSO4 solution containing LDHs for 10 min, and then stand for 48 hours to allow MXene and LDHs to fully adsorb ions, then centrifuge and collect the precipitate, dry it in a cool place, and then collect it for later use;
[0060] S2: Weigh about 50 mg of MXene and about 100 mg of LDHs after drying, weigh two cups of 100 mL of pure water in a beaker, and mark the two cups of pure water as A and B, respectively. Add 50 mg of MXene to beaker A and 100 mg of LDHs to beaker B, and ultrasonically disperse the two cups of solution for 10 minutes to prepare aqueous solutions of the two materials.
[0061] S3: A liquid battery tank with a size of 30cm×10cm×10cm is made of insulating plastic. The middle of the liquid battery tank is divided into a cathode area and an anode area by an insulating diaphragm. A titanium mesh inert electrode with a size of 10cm×10cm is placed in each of the two areas. A DC power supply is used as the power supply;
[0062] S4: Add MXene solution to the cathode area, add LDHs solution to the anode area, remove the insulating diaphragm, turn on the power supply, apply 10 V DC voltage, and set the reaction time to 12 h;
[0063] S5: After the reaction is completed, the liquid in the liquid battery tank is centrifuged using a centrifuge to collect the obtained MXene / LDHs heterojunction precipitate, which is dried in a cool place and then collected for later use.
[0064] The MXene / LDHs heterojunction prepared by the preparation method of the MXene / LDHs heterojunction self-assembly anti-corrosion coating is added to the coating. The specific method is as follows: weigh 5g of epoxy resin and 100mg of MXene / LDHs heterojunction, add the MXene / LDHs heterojunction to the epoxy resin, stir for 1 hour to mix them evenly, and obtain an active protective coating.
[0065] A Q235 steel plate with a size of 10 cm × 10 cm was selected. After surface treatment, a new coating doped with MXene / LDHs heterojunction and an undoped epoxy resin coating were coated on different areas. The coating thickness was about 200 μm. After coating, it was dried and the coating performance was evaluated by a chloride ion permeability test. The test results of the chloride ion penetration through the coating sheet are shown in Figure 2. Figure 3As shown in the figure, thanks to the MXene barrier effect and LDHs ion adsorption and exchange, the test value of the new coating doped with MXene / LDHs heterojunction is only 23.63% of that of the blank control sample, indicating that the new coating doped with MXene / LDHs heterojunction has strong resistance to chloride ion penetration. Therefore, MXene / LDHs heterojunction plays a key role in improving coating performance.
[0066] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing a MXene / LDHs heterojunction self-assembled anticorrosion coating, characterized in that: include: S1: adding MXene to an electrolyte solution, separating and drying the MXene in the electrolyte solution to obtain a MXene precipitate, adding LDHs to an electrolyte solution, separating and drying the LDHs in the electrolyte solution to obtain a LDHs precipitate; S2: The dried MXene precipitate is redissolved in a solvent and subjected to ultrasonic dispersion to obtain a MXene solution, and the dried LDHs precipitate is redissolved in a solvent to obtain an LDHs solution; S3: using an inert electrode and a DC power supply to make a liquid battery tank, and using an insulating membrane to divide the liquid battery tank into a cathode region and an anode region; S4: Add the MXene solution to the cathode area of the liquid battery tank, add the LDHs solution to the anode area of the liquid battery tank, remove the insulating diaphragm and turn on the power supply to make the MXene and LDHs react to form a MXene / LDHs heterojunction; S5: Centrifuge the mixed solution in the liquid battery tank, collect the MXene / LDHs heterojunction precipitate, and add the obtained MXene / LDHs heterojunction precipitate to the anti-corrosion coating.
2. The method for preparing the MXene / LDHs heterojunction self-assembly anti-corrosion coating according to claim 1, characterized in that: In S1, the electrolyte solution contains F - , Ca 2+ Mg 2+ 、Zn 2+ and Al 3+ .
3. The method for preparing the MXene / LDHs heterojunction self-assembly anti-corrosion coating according to claim 2, characterized in that: MXene and F - The molar ratio is greater than 1:
5.
4. The method for preparing the MXene / LDHs heterojunction self-assembly anti-corrosion coating according to claim 2, characterized in that: LDHs and Ca 2+ Mg 2+ 、Zn 2+ and Al 3+ The molar ratio is greater than 1:
5.
5. The method for preparing the MXene / LDHs heterojunction self-assembly anti-corrosion coating according to claim 1, characterized in that: In S1, the electrolyte solution containing MXene is subjected to ultrasonic treatment, static treatment and centrifugation treatment in sequence to obtain a MXene precipitate, and the electrolyte solution containing LDHs is subjected to ultrasonic treatment, static treatment and centrifugation treatment in sequence to obtain an LDHs precipitate.
6. The method for preparing the MXene / LDHs heterojunction self-assembly anti-corrosion coating according to claim 5, characterized in that: The static treatment time is greater than 24 hours.
7. The method for preparing the MXene / LDHs heterojunction self-assembly anti-corrosion coating according to claim 1, characterized in that: In S2, the solvent is pure water.
8. The method for preparing the MXene / LDHs heterojunction self-assembly anti-corrosion coating according to claim 1, characterized in that: In S2, the ultrasonic dispersion time is greater than 5 minutes.
9. The method for preparing the MXene / LDHs heterojunction self-assembly anti-corrosion coating according to claim 1, characterized in that: In S4, the power supply applies a voltage in the range of 5 volts to 10 volts.
10. The method for preparing the MXene / LDHs heterojunction self-assembly anti-corrosion coating according to claim 1, characterized in that: The reaction time of MXene and LDHs is greater than or equal to 6 hours.
Citation Information
Patent Citations
Ti3C2Tx and ZnAl-MoO4 LDH composite corrosion inhibitor and preparation method and composite coating thereof
CN114958056A
Preparation method of nano flower-shaped NiMn-LDH / MXene composite wave-absorbing agent
CN117720878A
Preparation method of anti-friction self-repairing conductive anticorrosive paint and paint
CN118006195A
Multifunctional lubricating anticorrosive material as well as preparation method and application thereof
CN118460068A